Cytogenetic analysis of A-, B-chromosomes and ZZ/ZW sex chromosomes of Characidium gomesi (Teleostei, Characiformes, Crenuchidae) - Maistro, Edson Luis; Jesus, Célia Maria de; Oliveira, Claudio; Moreira-Filho, Orlando; Foresti, Fausto (International Society of Cytology, 2004)
Different cytogenetic techniques were used to analyze the chromosomes of Characidium gomesi with the main objective of comparing the base composition of ZZ/ZW sex-chromosomes, B-chromosomes and the heterochromatin of A-chromosomes. The results of digestion of chromosomes with AluI restriction endonuclease (RE), silver and CMA3 staining, C-banding and fluorescence in situ hybridization (FISH) with the 18S rDNA probe suggested the existence of compositional differences between the heterochromatin of ZZ/ZW sex-chromosomes, A- and B-chromosomes, and indicated the presence of different numbers and morphology of B-chromosomes in the samples of this population.
Keywords: B-chromosomes; Characidium gomesi; Fish cytogenetics; Heterochromatin differentiation; ZZ/ZW sex chromosome system; Characidium; Characiformes; Crenuchidae; Teleostei